CONCEPTIONS OF LAND RECLAMATION IN THE POLISH OPENCAST MINING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1997)
In the paper the influence of surface mining on the environment is presented. The sizes of mining areas and depression funnels has been shown. Also are presented the amount of cover materials and the quantity of water pumped out from the mines in five regions of brown coal mining in Poland.Various conceptions of land reclamation are discussed, from the method of pioneer vegetation in the years of 1950 - 1970, trough selective excavation of the humus soil in the years 1970 - 1980, to conception of the direct introduction of the final type of vegetation.In the lost part of the paper three models of agricultural land remediation are discussed, as well as the yields of the cultivated plants on recultivated former mining areas.